Detection of Heterogeneity in Three-Dimensional Data Sequences: Algorithm and Applications - Evgueni A. Haroutunian; Irina A. Safaryan; Aram R. Nazaryan; Narine S. Harutyunyan (Изд-во НАН РА)
We present a nonparametric algorithm which allows reducing the investigations of changes of the joint distribution of chronologically ordered multidimensional random sequence to the investigations of some one-dimensional conditional distributions. The algorithm is implemented with the statistical software package R. The action of the program is demonstrated on applications.
Keywords: Mathematics; Algorithm